Aplikasi Online Mobile Repository System - Ricky, Michael Yoseph (ComTech: Computer, Mathematics and Engineering Applications, 2011)
In order to support the decision making process effectively and efficiently, a lot of companies invest in information technology for data management and storage. The information technology is emphasized in data storage of daily transactions in large numbers in a medium, so that data can be easily processed. Online Mobile Repository System is a system that uses a temporary storage system which is practical and can be accessed online. Thus, the system simplifies data access and organization anywhere and anytime. The design of this system uses the methods of literature review, interviews, field studies, and combined design studies. The research results in a data storage system which is organized, safe and structured to support the meeting process.